Evaluasi Usability Pada Aplikasi Pembelajaran Tari Menggunakan System Usability Scale (SUS) (Jurnal ICT : Information Communication & Technology, 2020)
The existence of dance in an area needs to be preserved so that it is not displaced by the entry of foreign cultural arts, The lack of interest of the younger generation in local culture needs to be watched out for because it has an impact on the sustainability of traditional dance. To introduce and motivate the younger generation to learn dance, an Android-based dance learning application has been developed. The purpose of this study was to evaluate the Android-based dance learning application, in the evaluation process involving 20 respondents to provide statements from the aspect of usability using the system usability scale (SUS) method consisting of the testing phase using 10 instruments for assessment, the data processing stage, the result analysis stage, and the result conclusion. The test results obtained a value of 79.37 with grade "B" means that the learning application that has been tested can be declared acceptable in the Acceptability Ranges category and it can be stated that the dance learning application is easy to use and can be used as a learning tools.